2014
DOI: 10.1007/s12035-014-8828-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol 24S-Hydroxylase Overexpression Inhibits the Liver X Receptor (LXR) Pathway by Activating Small Guanosine Triphosphate-Binding Proteins (sGTPases) in Neuronal Cells

Abstract: The neuronal-specific cholesterol 24S-hydroxylase (CYP46A1) is important for brain cholesterol elimination. Cyp46a1 null mice exhibit severe deficiencies in learning and hippocampal long-term potentiation, suggested to be caused by a decrease in isoprenoid intermediates of the mevalonate pathway. Conversely, transgenic mice overexpressing CYP46A1 show an improved cognitive function. These results raised the question of whether CYP46A1 expression can modulate the activity of proteins that are crucial for neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
1
31
1
Order By: Relevance
“…Second, we observed increased expression levels of ApoE and ABCA1 proteins, which are direct target genes regulated by LXRs, and recently reported to be expressed in vitro in primary culture of cortical neurons [ 48 ]. A previous study reported a 4-fold increase of ABCA1 levels in cerebral cortex and a 6-fold increase in hippocampus in APP/PS1 mice treated for 8 weeks as compared to untreated APP/PS1.…”
Section: Discussionmentioning
confidence: 79%
“…Second, we observed increased expression levels of ApoE and ABCA1 proteins, which are direct target genes regulated by LXRs, and recently reported to be expressed in vitro in primary culture of cortical neurons [ 48 ]. A previous study reported a 4-fold increase of ABCA1 levels in cerebral cortex and a 6-fold increase in hippocampus in APP/PS1 mice treated for 8 weeks as compared to untreated APP/PS1.…”
Section: Discussionmentioning
confidence: 79%
“…24-OHC also acts as either a pro-survival or pro-death factor in neurons. At physiological concentrations 24-OHC induces LXR signaling in neurons and generates a neuroprotective response [9,10], while at high concentrations 24-OHC inhibits LXR transcriptional activity [10], promoting a “necroptosis-like” death pathway in neurons [11,12]. Recently it has been proposed that the neuroprotective action of 24-OHC involves allosteric modulation of N-methyl-D-aspartate receptor (NMDAR) function, but this activity is the result of direct binding to NMDA receptors and not LXR activation [13,14], adding further complexity to the mechanisms by which LXR-activating oxysterols act on neurons.…”
Section: Cholesterol Homeostasis In the Cnsmentioning
confidence: 99%
“…Liver X receptors are important transcription factors (10)(11)(12), whereas NMDA receptors mediate excitatory transmission throughout the CNS and are involved in memory and learning (13). In addition, CYP46A1 activity or expression levels could affect protein prenylation and protein phosphorylation (14)(15)(16). Protein prenylation is linked to CYP46A1 via cholesterol biosynthesis and availability of the nonsterol intermediates used for prenylation (14,16).…”
mentioning
confidence: 99%